The cross, the plow and the skyline : contemporary science fiction and fantasy and the ecological imagination - Yanarella, Ernest J. (Irvine : BrownWalker Press, 2022)
"The apocalyptic, pastoral, and urban traditions have fundamentally shaped Western history and influenced American religion, culture, and politics. This book argues that these traditions have not only been decisive in giving form and substance to classic and modern American literature, but have been appropriated by contemporary science fiction. As a loosely connected set of cultural narratives, the Cross, the Plow, and the Skyline have through the medium of science fiction provided a bold vista on the future grounded in an emergent ecological imagination"--
Visions of the apocalypse : religion, politics, and science fiction -- Critical political theory and apocalyptic science fiction -- Interlude I : twenty-first century apocalyptic SF/F -- The Machine in the Garden Revisited : American Politics and Literary Pastoralism -- Critical hermeneutics and pastoral science fiction -- Ffin-de-siecle pastoralism and American populism -- Literary responses to the crisis of the 1890s and the populist challenge -- Interlude II : twenty-first century pastoral SF/F -- The telos of the city in social science and history -- Images of the city in contemporary science fiction -- Interlude III : twenty-first century urban SF/F -- The Gaia hypothesis and its shadow : Earth as Gaia and the specter of terra (terror)forming -- The darkness of Gaia : encountering the shadow of self and otherness in inner/outer space -- Interlude IV : the ecological imagination in twenty-first century SF/F.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
eBooks on EBSCOhost
Keywords: Science fiction, American -- History and criticism; Fantasy fiction, American -- History and criticism; Ecology in literature; Religion in literature; Politics in literature; Religion dans la littérature.; Ecology in literature; Fantasy fiction, American; Politics in literature; Religion in literature; Science fiction, American; Criticism, interpretation, etc